The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.5606/tgkdc.dergisi.2023.24330
|View full text |Cite
|
Sign up to set email alerts
|

Dilated sinuses of Valsalva subsequent to type A dissection surgery: Is reoperation inevitable?

Abstract: Background: This study aims to investigate the dilation of sinus valsalva in patients who underwent aortic repair due to type A aortic dissection and to evaluate its progression. Methods: Between January 2004 and December 2019, a total of 68 patients (50 males, 18 females; mean age: 54.2±10.1 years; range, 30 to 82 years) who underwent root-preserving surgery and followed for at least one year in the outpatient setting were retrospectively analyzed. The patients were divided into two groups according to dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…In their retrospective study regarding aortic root management, Kose et al[ 1 ] studied 68 patients with a mean age of 54.2±10.1 years for an average of 4.9±3.1 years following a root protective surgery (supracoronary graft interposition without commissural resuspension). Of 64 patients, 32 (47.06%) had sinus of Valsalva (SOV) dilatation (SOV diameter: 5.23±0.61 cm), while 36 (52.94%) had normal SOV (SOV diameter: 3.74±0.43 cm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their retrospective study regarding aortic root management, Kose et al[ 1 ] studied 68 patients with a mean age of 54.2±10.1 years for an average of 4.9±3.1 years following a root protective surgery (supracoronary graft interposition without commissural resuspension). Of 64 patients, 32 (47.06%) had sinus of Valsalva (SOV) dilatation (SOV diameter: 5.23±0.61 cm), while 36 (52.94%) had normal SOV (SOV diameter: 3.74±0.43 cm).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the diameter of the aortic root above ≥4.5 cm was one of the indications of the root replacement. [ 6 ] The reason that Kose et al's[ 1 ] study found a preoperative SOV diameter of ≥4.05 cm as a reoperation risk factor could be not resuspending the commissures and having a younger patient population in the study. In my professional opinion, further studies are necessary to correlate the preoperative SOV diameter and reoperation risk.…”
Section: Introductionmentioning
confidence: 99%